(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research demonstrates the use of linear programming in maximizing the proﬁt. It applies the concept of simplex method; a method in linear programming to solve industrial problems that aims to maximize the proﬁt. The Magdalena Dairy Raisers Association specializes in production of dairy products. Three different varieties of dairy products were observed. The data was simulated using MATLAB; a fourth-generation programming language and numerical analysis environment that creates data visualization and user interfaces (UI), calculates matrices, and develops and runs algorithms. The results show that using the Linear Programming Model, we obtain the total revenue of each dairy product with an increase of 108.17% for Fresh Milk, 12.10% for Choco Milk, and 35.95% for Milk O Jel from their previous revenue. As a result, we achieved our goal to maximize the net proﬁt with a total increase of 151.16%..